Program Rehabilitasi Masjid Nurul Huda Dalam Rangka Memperkuat Kemanunggalan TNI–Rakyat - Agung Prapsetyo; Luluk Kristatnto; Kiki Lestari; Frangky Silitonga; Nurtjahyono Nurtjahyono (JURNAL NAGARA BHAKTI, 2026)
Community service is a manifestation of the Tri Dharma of Higher Education, aiming to integrate science with the real needs of society. For military educational institutions, this activity has a strategic dimension as an instrument of Military Operations Other Than War (OMSP) to realize the unity of the Indonesian National Armed Forces (TNI) with the people. This article analyzes the physical rehabilitation of the Nurul Huda Mosque in Bendo Village, Boyolali, by the Military Academy's Civil Defense Engineering Study Program. Using the Participatory Action Research (PAR) method, this community service involved collaboration between 29 personnel (lecturers, cadets, and staff) and local residents. The activity stages included planning, preparation, physical implementation (painting and ceiling installation), and sustainability evaluation. The results showed a significant improvement in the quality of worship infrastructure and the creation of social cohesion through community service. Technically, the rehabilitation successfully optimized the use of local materials and self-employed labor for budget efficiency. Sociologically, this program strengthened public trust in the TNI and shaped the character of humanistic soldiers. The study's conclusions emphasize that adequate worship infrastructure is a central hub for spiritual development and regional resilience at the village level.